53.4k views
0 votes
3x - 5y = 10 6x + 3y = -6 Marybeth is going to solve this problem by multiplying the top equation by -2. If she does this and combines the equations, what does she get? A) -13y = -26 B) -7y = 14 C) -2y = 4 D) 13y = -26

2 Answers

4 votes

Answer:

multiplying and simplifying the above two equations gives answer as 13y = -26

Explanation:

User Andrii Shvydkyi
by
5.7k points
2 votes

On multiplying with -2 in the equation
3 x-5 y=10
given in the question we get as 13y = -26

Answer: Option(d)

Step by Step Explanation:

Solution;

The given two set of equations such as


3 x-5 y=10
(Equation 1)


6 x+3 y=-6
(Equation 2)

Also given, Marybeth multiplies the first equation by -2

After multiplying with -2 in first equation we get


-2 *[3 x-5 y]=-2 *[10]


-6 x+10 y=-20

Adding the newly obtained equation 1 and Equation 2,


[-6 x+10 y=-20]+[6 x+3 y=-6]

Adding the like terms x, y and constants we get


6 x+3 y+(-6 x)+10 y=-6+(-20)


0 x+13 y=-6+(-20)

13y=-26

Result:

Thus on multiplying and simplifying the above two equations gives answer as 13y = -26

User Yuval Peled
by
6.0k points